2013
DOI: 10.1590/s0100-83582013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia da trapoeraba como indicador para tolerância ao herbicida glyphosate

Abstract: Rotineiramente, tem sido desconsiderada a contribuição do estádio de desenvolvimento das espécies de plantas daninhas nas análises de tolerância ou resistência a herbicidas, o que pode resultar em divergências entre a pesquisa teórica e a aplicação prática dos dados. Nesse sentido, este trabalho foi desenvolvido com o objetivo de avaliar a resposta biológica da trapoeraba (Commelina benghalensis), comparativamente ao capim-marmelada (Brachiaria plantaginea), a aplicações de doses do herbicida glyphosate, em se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
1
11
0
10
Order By: Relevance
“…of glyphosate were necessary to reach LD50 of the same population, when considering preflowering plants. In the same work, glyphosate dose necessary to control pre-flowering Brachiaria plantaginea was five times fold than application on cotyledon leaves plants (Dias et al, 2013). Christoffoleti et al (2005) and Ribeiro (2008) also reported the interference of plants phenological stage on glyphosate efficacy.…”
Section: Resultsmentioning
confidence: 86%
“…of glyphosate were necessary to reach LD50 of the same population, when considering preflowering plants. In the same work, glyphosate dose necessary to control pre-flowering Brachiaria plantaginea was five times fold than application on cotyledon leaves plants (Dias et al, 2013). Christoffoleti et al (2005) and Ribeiro (2008) also reported the interference of plants phenological stage on glyphosate efficacy.…”
Section: Resultsmentioning
confidence: 86%
“…Possivelmente essa característica de rebrota se fundamenta no grande desenvolvimento do sistema radicular de T. paniculatum, característica essa descrita para várias espécies da família das portulacaceas (Carvalho, 2013).…”
Section: Resultsunclassified
“…Situação essa observada para a espécie Commelina sp. que a medida em que se aumentaram as doses de glyphosate aplicadas, essas tenderam a se tornar menos efetivas, demonstrando certa tolerância, que foi diretamente relacionada com a fase mais avançada de desenvolvimento das plantas (Dias et al, 2013). Semelhante resultado foi observado por Cesarin et al (2013) para a planta daninha Sisyrinchium micranthum Cav.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The development of plants is related with several phenological stages, presenting greater or limited sensibility to the application of herbicides (Dias et al, 2013). After having emerged, these plants quickly dominate the environment, either by the development of a vigorous root system or by taking over the available space with the greatest light interception (Horak & Loughin, 2000;Carvalho et al, 2008).…”
Section: Introductionmentioning
confidence: 99%